PRZYWRÓCENIE INSTYTUCJI PETYCJI W POLSKIM PORZĄDKU PRAWNYM - Wójcicka, Ewa (Wydział Prawa i Administracji UAM, 2006)
After many years of discontinued existence of the institution of petition in the Polish legal order, the Constitution of the Republic of Poland restored it in 1997. Its new shape is a synthesis of the five projects that supported the institution, and also of variant drafts of the Constitution and the experts’ reports and opinions, all of which had contributed to the final result of the Commission’s work. A number of controversies arose in the discussion concerning the legal form of the petition. They were: who was entitled to take advantage of this new law, the criterium of the interest that decided about the usage of the institution, and the problem of a possible collision of the petition with the protection of privacy. In spite of clear differences in their opinions, the Members of the Commission approved the final draft o f this law on the 39th session. The final version of the Constitution granted everyone the right to submit petitions in the public interest, or in his or her own interest or in the interest of another person, with that person's consent, to organs of public authority, as well as to organisations and social institutions in connection with the performance of their prescribed duties within the field of public administration.
RESTORATION OF THE INSTITUTION OF PETITION IN THE POLISH LEGAL SYSTEM